e-pest surveillance system for soybean (Glycine max) and cotton (Gossypium spp) crops - Singh, Niranjan; Jeyakumar, P; Bambawale, O M; Vennila, S; Kanojia, A K; Bhagat, S; Sathyakumar, S (The Indian Journal of Agricultural Sciences, 2012)
A web-based decision support system called e-pest surveillance system was developed and implemented for effective and regular pest monitoring in soybean [Glycine max (L.) Merrill] and cotton (Gossypium spp) crops in Maharashtra. Epidemics of Spodopetra litura (Fab.) occurred during 2008–09 in an area of 1.46 million ha caused loss of 0.85 million tonnes and monetary loss of INR 1.39 billion, which led to the immediate need for systematic area wide pest monitoring. Application of web technologies speeded up the whole process of pest surveillance and appropriate actions to be taken to manage pests by the farmers. The System consists of three major components, viz. a database, an offline data capture and online data reporting and advisory applications. Information of the incidence of key pests of selected crops collected through regular monitoring by State Department of Plant Protection personnel at farmer’s field was fed into the offline data capture application deployed at their computers and subsequently transferred to central database. Pest management experts from State Agriculture Universities (SAUs) accessed the pest reports generated on the central database through online reporting and advisory application. Decisions of pest management were made on the basis of these reports by state pest experts and issued as advisories to farmers through short message service (SMS) for implementation. This describes the structure and functions of the e-pest surveillance system, which seeks to be first of its kind in Indian agriculture for pest management at farmer’s field level.